Enteral lactoferrin supplementation for very preterm infants: a randomised placebo-controlled trial - Griffiths, J; Jenkins, P; Vargova, M; Bowler, U; Juszczak, E; King, A; Linsell, L; Murray, D; Partlett, C; Patel, M; Berrington, J; Dorling, J; et al. (Elsevier, 2019)
Background Infections acquired in hospital are an important cause of morbidity and mortality in very preterm infants. Several small trials have suggested that supplementing the enteral diet of very preterm infants with lactoferrin, an antimicrobial protein processed from cow’s milk, prevents infections and associated complications. Methods In this randomised, placebo-controlled trial, very preterm infants (born before 32 weeks’ gestation) in 37 UK hospitals were allocated randomly (1:1) within 72 hours after birth to receive enteral bovine lactoferrin (150 mg/kg/day; maximum 300 mg/day) versus sucrose (same dose) once daily until 34 weeks’ postmenstrual age. Web-based randomisation minimised for recruitment site, gestation (completed weeks), sex, and single versus multifetal pregnancy. Parents, caregivers and outcomes assessors were unaware of group assignment. The primary outcome was microbiologically-confirmed or clinically-suspected late-onset infection (occurring >72 hours after birth). The trial was registered with the International Standard Randomised Controlled Trial Number 88261002. Findings We recruited 2203 participants between May 2014 and September 2017. Four infants had consent withdrawn or unconfirmed leaving 1098 infants in the lactoferrin group and 1101 in the sucrose group. Primary outcome data for 2182 infants were available for inclusion in the intention-to-treat analyses. In the intervention group, 316/1093 (28.9%) infants acquired a late-onset infection versus 334/1089 (30.7%) in the control group: risk ratio (RR) adjusted for minimisation factors 0.95 (95% confidence interval [CI] 0.86, 1.04). Pre-specified subgroup analyses did not show statistically significant interactions for gestation at birth (completed weeks’) or type of enteral milk received (human, formula, or both). Interpretation Enteral supplementation with bovine lactoferrin does not reduce the incidence of late-onset infection in very preterm infants.